Why Aceh-Indonesia Conflict Resolution can’t be Copy-Paste in Bangsamoro-Philippines Issue? - Jatmika, Sidik; Sumanang, Nanang; Marlinda, Ajeng Puspa; Nabilazka, Chalilla Raihan; Jatmika, Muhammad Indrawan (Universitas Muhammadiyah Yogyakarta, 2022)
This article focuses on conflict resolution in Aceh, Indonesia, and Bangsamoro, Phillipines, as a comparative study. The two different regions have at least two similar characteristics: both are recognised by central government as widely autonomous provinces compared to other provinces, and both have same problems with revolutionary groups that attempt to withdraw from central government. This qualitative research aims to examine conflict resolution process and result in both local governments. The main objective is to identify similarities rational choice (survival, security, economy/welfare, prestige, and influence) especially how political elites would still feel enjoy to conduct those agreements in both regions. The findings confirm that both GAM (Aceh) and MILF (Bangsamoro) have similar political preference sequence, but such of MNLF factions still continues their military movements. It is argued that Aceh-Indonesia conflict resolution could not automatically be applied in the Bangsamoro-Philippines issue.